Impaired decision-making in symptomatic anorexia and bulimia nervosa patients: a meta-analysis. Issue 16 (1st September 2015) - Guillaume, S.; Gorwood, P.; Jollant, F.; Van den Eynde, F.; Courtet, P.; Richard-Devantoy, S.
Abstract : Background: Impaired decision-making is a potential neurocognitive phenotype of eating disorders. It is therefore important to disentangle the decision-making deficits associated with the eating disorder subtypes and determine whether this putative impairment is a state or trait marker of the disease or more related to starvation. We systematically reviewed the literature on decision-making in eating disorders and conducted a meta-analysis to explore its role in anorexia nervosa (AN), bulimia nervosa (BN) and binge-eating disorder (BED). Method: A search of the Medline and EMBASE databases and article references was performed. A total of 23 studies (2044 participants) met the selection criteria. When the Iowa gambling task (IGT) was used in at least three of the studies, a meta-analysis was run. Results: IGT performance was significantly worse in patients with an eating disorder diagnosis (AN, BN or BED) compared with healthy controls, indicating that eating disorders have a negative effect on decision-making. Hedges' g effect sizes were moderate to large (−0.72 in AN, −0.62 in BN, and −1.26 in BED). Recovered AN patients had IGT scores similar to those of healthy controls. Restrictive AN patients had significantly lower IGT net scores than purging AN patients, and both AN subtypes had worse performances than healthy controls. Age and body mass index did not explain results. Conclusions: Decision-making was significantly altered in patients with eating disorders. Poor decision-making was more pronounced during the acute phase than in the recovered state of AN. Nutritional status during the acute phase of the disease did not seem to influence decision-making skills.